The Politics of Language Suppression in the Novel Cadl: A Novel Without the Letter E by Triskaidekaman (A Sociological Study of Literature) - Mohammad Wahyudi Wahyu; Natalia Endah Hapsari (Program Studi Tadris Bahasa Indonesia Institut Agama Islam Negeri Lhokseumawe, 2025)
This research examines the phenomenon of language silencing in the novel